Continuous acceleration of neural activity of the GnRH pulse generator during chronic peripheral infusion of neurokinin 3 receptor agonist in goats - Takashi YAMAMURA; Hiroaki OKAMURA; Yoshihiro WAKABAYASHI (The Society for Reproduction and Development, 2023)
Secretion of pulsatile gonadotropin-releasing hormone (GnRH) is essential for reproduction. Kisspeptin neurons in the arcuate nucleus (ARC), which coexpress neurokinin B (NKB) and its receptor (NK3R), are believed to be components of the GnRH pulse generator that regulates pulsatile GnRH secretion. We examined the effects of peripheral infusion of senktide, an NK3R selective agonist, on GnRH pulse generator activity by monitoring multiple unit activity (MUA) in the goat ARC. Previous studies have shown that characteristic increases in MUA (MUA volleys) reflect GnRH pulse generator activity. Senktide was infused intravenously or intravaginally for 2 h while recording MUA. Both infusions significantly increased the MUA volley frequency compared with the control. These results demonstrate that peripherally administered senktide acts centrally to sustainably accelerate the neural activity of the GnRH pulse generator throughout the infusion period. This suggests the possibility of practical applications of NK3R agonists for improving reproductive activity in farm animals.